Insect Fauna Associated with Exposed Pig Carcasses in Southern Brazil - Ries, Ana Carolina; Blochtein, Betina (EntomoBrasilis, 2015)
The knowledge of insect patterns visiting decomposing carcasses and the analysis of parameters related to their presence help determine the post-mortem interval (PMI). This information depends on regional studies because the diversity of insects and the environmental conditions interfere in this process. The aim of the study was to analyze the insect fauna that colonizes carcasses of pigs exposed in different stages of decomposition in the study area. The experiment was conducted in southern Brazil using three domestic pigs (Sus scrofa Linnaeus) that were killed on site. Adult insects associated with carcasses were sampled daily using an insect net, manual collection and pitfall traps. Statistical tests were performed to evaluate the diversity of insects. During the process of decomposition (14 days), Scarabaeidae (25%) and Calliphoridae (23%) species were the most abundant of all of the samples. The diversity of insects is distinguishable when all parameters are analyzed. The Black Putrefaction (IV) stage exhibited the highest diversity according to the applied methods. The succession pattern was established from the species dominance index: Fresh stage - Lucilia eximia Wiedemann (Diptera, Calliphoridae); Chromatic and Bloat - Chrysomya albiceps (Wiedemann) (Diptera, Calliphoridae); Black Putrefaction and Skeletonization - Aphodiinae sp. 1 (Coleoptera, Scarabaeidae). Entomofauna Associada a Carcaças de Suínos Expostas no Sul do Brasil Resumo. O conhecimento dos padrões de insetos que visitam carcaças em decomposição e a análise dos parâmetros relacionados a sua presença auxilia na determinação do intervalo post-mortem (IPM). Estas informações dependem de estudos regionais, pois a diversidade de insetos e as condições ambientais interferem neste contexto. O objetivo do estudo foi analisar a entomofauna que coloniza carcaças expostas em diferentes estágios de decomposição na área de estudo. O experimento foi conduzido no sul do Brasil utilizando três porcos domésticos (Sus scrofa Linnaeus), abatidos no local. Insetos adultos associados às carcaças foram amostrados diariamente com rede entomológica, coleta manual e armadilhas pitfall. Foram realizados testes estatísticos para avaliar a diversidade de insetos. Durante o processo de decomposição (14 dias), espécimes de Scarabaeidae (25%) e Calliphoridae (23%) foram os mais abundantes, considerando-se a totalidade das amostras. A diversidade de insetos é distinguível quando são analisados todos os parâmetros. A fase de Putrefação negra (IV) exibiu a maior diversidade de acordo com os métodos aplicados. O padrão de sucessão foi estabelecido a partir do índice de dominância das espécies: fase Fresca - Lucilia eximia Wiedemann (Diptera, Calliphoridae), fase Cromática e de Inchamento – Chrysomya albiceps (Wiedemann) (Diptera, Calliphoridae), e fase de Putrefação Negra e de Esqueletização – Aphodiinae sp. 1 (Coleoptera, Scarabaeidae).